Water Resources Management: Coexistence and Conflict in Semiarid Brazil - Dias, Thiago Ferreira; Valença, Daniel Araújo; de Araújo, Iriane Teresa; Gomes, Rayane Cristina de Andrade; Maia Jr., Ronaldo Moreira (Desenvolvimento em Questão, 2016)
The paper analyzes water management in the Brazilian semiarid region with emphasis on aspects of coexistence and conflicts over access in rural areas. Experiences of social coexistence in semiarid technologies from the joint to the Brazilian semiarid (ASA) and water conflicts from cases of irrigated areas in the states of Ceará and Rio Grande do Norte are explained. For this purpose, we used a qualitative approach through the use of primary and secondary data. The cases provide concrete actions that articulate civil society and the State in favor of the common good. The results indicate that the policy articulated by the ASA there is a governance process in which there are links between the forums of civil society and the interfaces in the planning and implementation of public policies in building public agenda that can bridge the gap between planning, deployment, management and improvement of this policy. In the second case the policy is implemented exclusion and allocation of those communities, placing them on the margins of development, scrapping its links with the territory. The water is not seen from the perspective of the common good and the communities are perceived as an obstacle to "development". Finally, it outlines themselves from the cases under study, with the idea that limiting access to water in the semiarid region, reflects the precarious welfare and perpetuation of relations of dependency, paternalism and clientelism high proportion of the population rural Brazilian semiarid.